A Systematic Analysis of the Vulnerability of Buildings to Localised Collapse - Janssens, Victoria; O' Dwyer, Dermot W (Civil-Comp Press, 2009)
This paper presents a methodology to assess the extent of damage to a multi-storey structure due to localised collapse. This is accomplished through the design of an algorithm, to track progressive collapse in a structure, and its implementation as a computer program. This program is based on the alternative path method of analysis, and involves systematically removing individual elements from the structure following their failure. The algorithm works by increasing the applied load and monitoring the formation of plastic hinges, and the development of unstable compression members. The formation of such mechanisms can cause localised damage or may lead to progressive collapse. By systematically considering the effects of damage to all members in a structure, the algorithm can identify whether a structure is unduly sensitive to the effects of localised damage.
The Twelfth International Conference on Civil, Structural and Environmental Engineering Computing
PUBLISHED
Keywords: robustness; progressive collapse; accidental actions; elasto-plastic analysis; alternative load path; structural analysis; vulnerability